Clinical evaluation of surgical affections and postoperative outcomes in ruminants at a Veterinary Teaching Hospital Babugonj in Barishal, Bangladesh (Asian Journal of Medical and Biological Research, 2026)
Ruminants play a vital role in the livestock economy of Bangladesh; however, they are frequently affected by various surgical conditions that compromise productivity and animal welfare. A hospital-based cross-sectional study was conducted at the Veterinary Teaching Hospital, Babuganj, Barishal, Bangladesh from 1 December 2024 to 28 February 2025 to determine the incidence, pattern, and outcomes of surgical affections in ruminants. A total of 58 ruminants were examined, among which 19 animals were diagnosed with surgical conditions, giving an overall incidence of 32.75%. The incidence was slightly higher in cattle (34.37%) compared to goats (30.67%). The most frequently recorded surgical conditions included medial patellar fixation, umbilical hernia, atresia ani, knuckling, intramedullary bone pinning, caesarean section, hoof overgrowth, fractures, and subcutaneous cysts. Species-wise analysis showed a statistically significant association between species and type of surgical affection (χ² = 19.00, P = 0.015). One-way ANOVA revealed a highly significant variation in body weight among different surgical conditions (F = 118.57, P < 0.001). Postoperative follow-up indicated successful recovery in all surgically treated cases with appropriate clinical management. The study provides baseline hospital-level data on the distribution of surgical affections in ruminants in the Barishal region of Bangladesh.Asian J. Med. Biol. Res. 2026, 12(2), 34-46